A study of investor response to new product launching: a competitive strategy approach / Eliyani Linda R. and Utami Wiwik. - Rosenta, Eliyani Linda; Wiwik, Utami (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study examines investor response to the announcement of new product launching. The research design was event study methodology,where the researchers want to test empirically the investor response to new product launching by considering the business strategy used by each firm. Population of study was all firms listed in Indonesia Stock Exchange, except firms in the financial industry during 2009-2012. The samples were firms that announced their new products, and were selected based on certain criteria. During the period there were 63 announcements of new product launching from 27 firms. Rivals were identified for comparative analysis purpose. All firms in the same sub sector were considered as rivals. The announcing firms and its rivals were identified into competitive strategy group (strategic substitutes, strategic complements), by employing Competitive Strategy Measure in reference to Sundaram, John and John (1996). In this study the announcement-period was two days before and after the announcement date. The analysis was performed by comparing, before and after, Cumulative Abnormal Return (CAR) for each event of the announcing firms. The average cumulative abnormal return of the announcement period of announcing firms was then compared between strategy groups (strategic substitutes, strategic complements). In addition, CAR was compared between announcing firms and its rivals in strategic substitutes group, and in strategic complements group. The comparative study showed that the announcing firms in strategic substitutes group gained higher return than the announcing firms in strategic complements group. There was no significant difference between the announcing firms and its rivals, neither in strategic substitutes nor in strategic complements.